Perceived Benefits and Challenges of Using Note-Taking in Intensive Listening among University Students - Tiara Azzahra Marpaung; Anggun Citra Sari Dewi (International Journal of Innovation and Education Research, 2025)
One of the best strategies to support listening comprehension is note-taking strategy. In this study, students' perceptions of the benefits and challenges of using note-taking strategies were explored especially in Intensive Listening class. A mixed-methods approach was used involving 28 first-semester students in the English Language Education Department at the University of Bengkulu. Quantitative data were collected through a Likert-scale questionnaire adapted from Dunkel and Davy (1989) which consist of 19 questions in 3 subparts, while qualitative data were obtained through semi-structured interviews. Findings of the study indicate that students view note-taking positively, as it helps them capture main ideas, organize information, reduce cognitive load, and increase focus during listening activities. Students also believe that note-taking strategy improves their performance on listening tasks and exams. However, challenges such as limited English proficiency, difficulty multitasking while listening, and a lack of effective note-taking techniques were identified. This study demonstrates the need for explicit instruction in note-taking strategies to maximize their effectiveness in Intensive Listening classes.